DIGITAL AND APPROPRIATE TECHNOLOGY-BASED WOMEN’S ECONOMIC EMPOWERMENT: COLLABORATIVE COMMUNITY ENGAGEMENT OF UNIBA KKM STUDENTS WITH WOMEN COMMUNITIES IN DALUNG VILLAGE - Aqidah, Aniyatul; Auliani, Tia; Mutia, Lesti; Syaharani, Difa; Oktariandi, Raden Rivanda; Najibulloh, Najibulloh; Puspa, Rani (International Journal of Engagement and Empowerment (IJE2), 2025)
Digital transformation and the application of appropriate technology are pivotal in supporting women’s economic empowerment, particularly among household-based micro, small, and medium enterprises (MSMEs). This community engagement program, conducted by the KKM Group 03 students of Universitas Bina Bangsa (UNIBA) in Dalung Village, Serang City, combined two key initiatives: (1) Socialization of MSME Digitalization for members of the Darussalam Women’s Religious Study Group, and (2) Introduction of Appropriate Technology (AT) for the Red Chili Women Farmer Group (KWT). The program aimed to enhance digital literacy among women entrepreneurs, introduce social media-based marketing strategies, and promote simple innovations such as gravity-fed automatic irrigation tools and eco-enzyme production. The outcomes indicated improved understanding, skills, and enthusiasm among participants in utilizing technology to support their businesses and household farming activities. This program serves as a multidisciplinary collaborative model for community empowerment, replicable in similar contexts.